Methyleugenol protects against t-BHP-triggered oxidative injury by induction of Nrf2 dependent on AMPK/GSK3Î² and ERK activation - Junfeng Zhou; Xiaoyuan Ma; Yan Cui; Yang Song; Lei Yao; Yuanyuan Liu; Shanshan Li (Elsevier, 2017)
Methyleugenol (Mlg), a natural ingredient of many herbs and used as a flavoring substance in dietary products, inhibits inflammation and oxidative stress. The aim of the study is to explore the antioxidative potential of Mlg against tert-butyl hydroperoxide (t-BHP)-triggered oxidative injury and the involvement of antioxidative mechanisms. Our findings indicated that Mlg exposure significantly alleviated t-BHP-stimulated cytotoxicity, suppressed reactive oxygen species (ROS) generation, and increased superoxide dismutase (SOD) and glutathione (GSH) levels, which were related to the induction of the glutamate-cysteine ligase catalytic/modifier (GCLC/GCLM) subunit, heme oxygenase-1 (HO-1), and NAD (P) H: quinone oxidoreductase (NQO1) largely dependent upon upregulating the nuclear factor-erythroid 2-related factor 2 (Nrf2) induction, inhibiting the Keap1 protein expression, and heightening the antioxidant response element (ARE) activity. Additionally, Mlg exposure obviously induced AMP-activated protein kinase (AMPK), glycogen synthase kinase 3Î² (GSK3Î²) and extracellular signal-regulated kinase (ERK) phosphorylation, but AMPK and ERK inhibitors treatment exhibited effectively reduced levels of Mlg-enhanced Nrf2 nuclear translocation, respectively. Furthermore, Mlg exposure significantly lessened t-BHP-induced cytotoxicity and ROS production which were evidently abolished by treatment with AMPK and ERK inhibitors and Nrf2 siRNA. Accordingly, Mlg might exhibit a protective role against t-BHP-triggered cytotoxicity via the activation of the AMPK/GSK3Î²- and ERK-Nrf2 signaling pathways. Keywords: Methyleugenol, Oxidative stress, Reactive oxygen species, Nrf2